-3+2v-1+4=v-3

Simple and best practice solution for -3+2v-1+4=v-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3+2v-1+4=v-3 equation:


Simplifying
-3 + 2v + -1 + 4 = v + -3

Reorder the terms:
-3 + -1 + 4 + 2v = v + -3

Combine like terms: -3 + -1 = -4
-4 + 4 + 2v = v + -3

Combine like terms: -4 + 4 = 0
0 + 2v = v + -3
2v = v + -3

Reorder the terms:
2v = -3 + v

Solving
2v = -3 + v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-1v' to each side of the equation.
2v + -1v = -3 + v + -1v

Combine like terms: 2v + -1v = 1v
1v = -3 + v + -1v

Combine like terms: v + -1v = 0
1v = -3 + 0
1v = -3

Divide each side by '1'.
v = -3

Simplifying
v = -3

See similar equations:

| -4n+3n=-15+n+4+5 | | 4p+25=(6-3)-3(4-3p) | | -12-3m=4m-5m | | 7a-11=-3+6a | | -4+-22=-7x+14 | | 12+3n=3n-6n | | -10+6+4h+3h=6h-4+3 | | 300x^2-120x-8=0 | | W(a)=2a | | H(a)=a^3 | | 100x^3-60x^2-8x=0 | | 4p-7=5p+9 | | 2p+3q=28 | | 7v+10=7v+20 | | 2x+5=x+35 | | 4(3+4y)+7y=-6 | | -8-3*m=19 | | 13+6*n=67 | | x^2+5x=-25 | | 32-9*n=140 | | 5-2*n=7 | | 5-x=8x-1 | | 8d-(4d+2)= | | 3(34-4y)+5y=39 | | 15x+14x-8=0 | | 16x^4+8x^2-15=0 | | 3r-5=2(-4-9) | | 7m-8=13 | | 4=5k+9 | | 3x^2-x^2-2x=0 | | 2(x^2+4x+8)=170 | | 5x+1=625 |

Equations solver categories